equation list - Non-Homogeneous Equations y(x) = yc + yp if...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Non-Homogeneous Equations y(x) = y c + y p if f(x) y c y p = A*f(x) (when f(x) is exp or polynomial) y p = Asin(x) + Bcos(x) (when f(x) is sin/cos) polynomial terms: (Ax 2 + Bx + C) even if some of the coefficients are 0 if f(x) = y c multiply “bad” term by smallest power of x that will eliminate duplication Variation of Parameters If y’’ + P(x)y’ + Q(x)y = f(x) & y c =c 1 y 1 + c 2 y 2 Y p = -y 1 [y 2 f(x))/w] + y 2 [y 1 f(x)]/w Where w=(y 1 )(y’ 2 ) – (y 2 )(y’ 1 ) Undamped Forced Oscillation mx’’ + kx = F 0 cos( ϖ t); ϖ 0 = (k/m) x c = c 1 cos( ϖ 0 t) + c 2 sin( ϖ 0 t) x p = [(F 0 /m)/( ϖ 0 2 - ϖ 0 )]cos( ϖ t) if ϖ 0 = ϖ resonance ϖ 0 is internal & ϖ is external frequency Damped Forced Oscillations mx’’ + cx’ + kx = F(t) x c is the transient solution x p = stable solution amplitude of x p is called forced amplitude. It’s max value is called practical resonance Method of Elimination Solve one equation in terms of another Take the derivative of one equation
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.
Ask a homework question - tutors are online